Investigation of extraneous water inflow to separated sewage systems by hatch - Bogusławski, Bartosz; Głowacka, Anna; Sobczak, Piotr (Instal, 2021)
Extraneous water poses a substantial problem in the exploitation of separate sewerage systems. Many studies show that accidental water can reach 66% of the annual sewage supply to the system. Field observations lead to the supposition that a considerable stormwater volume could permeate to sewage system by hatches. In the investigation measurement device mounted under the hatch was used. The aim was to determine a real inflow to the sewage well during precipitation. In the two months of research, the whole inflow by hatch was 3,2 m3 and a maximum daily inflow was 801,8 dm3. The influence of daily precipitation on pump station flow was examined. In the two days with the highest rain height, the pump station flow was 63% and 118% higher than the average flow in the considered period.